1991
DOI: 10.1128/aac.35.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Anti-human immunodeficiency virus synergism by zidovudine (3'-azidothymidine) and didanosine (dideoxyinosine) contrasts with their additive inhibition of normal human marrow progenitor cells

Abstract: The anti-human immunodeficiency virus (HIV) activity and hemopoietic toxicity of zidovudine (AZT) and didanosine (dideoxyinosine; ddl), alone and in combination, were assessed in a variety of cell types. AZT was more potent than ddl as an inhibitor of HIV in vitro. Synergistic inhibition of HIV by the combination of these agents was observed in MT4 cells, peripheral blood lymphocytes, and macrophages. Toxicity assessment in vitro by using progenitor (erythroid and granulocyte-macrophage) colony-forming assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…This is consistent with previous data showing AZT to be without an effect on rNTP pools (Cox, 1991). The lack of effect of the combination of AZT + ddl upon dNTP or rNTP pools is consistent with observations that the toxicity of this combination is only additive and not synergistic (Schinazi et al, 1990;Dornsife et al, 1991). AZT was phosphorylated more effectively than ddl at the same concentration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is consistent with previous data showing AZT to be without an effect on rNTP pools (Cox, 1991). The lack of effect of the combination of AZT + ddl upon dNTP or rNTP pools is consistent with observations that the toxicity of this combination is only additive and not synergistic (Schinazi et al, 1990;Dornsife et al, 1991). AZT was phosphorylated more effectively than ddl at the same concentration.…”
Section: Discussionsupporting
confidence: 72%
“…The combination of AZT and ddl was first shown by Schinazi et al to exhibit, in vitro, synergistic inhibition of HIV (Schinazi et al, 1990;Dornsife et al, 1991). These two nucleoside analogues rely on intracellular enzymes for metabolism to their active 5'-triphosphate forms, AZT-TP and ddA-TP respectively, which then inhibit reverse transcriptase (RT) (Furman et al, 1986;Hao et al, 1988;Huang et al, 1990;Tornevik et al, 1991;De Clercq, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The growth inhibition results described here and elsewhere (Averett et al, 1991) suggested that adenosine deaminase activity plays a role in decreasing the toxicity of adenosine arabinoside and in increasing the toxicity of % of Control ara-M, For this reason, it was desirable to quantitatively compare the substrate efficiency of the arabinosides of adenine, 6-methoxypurine, and 6-ethoxypurine. Adenosine deaminase was able to convert each of these compounds to ara-H, The reaction product was confirmed as ara-H by spectroscopy (Methods and Experimental procedures).…”
Section: Resultsmentioning
confidence: 99%
“…The potent and selective activity of 6-methoxypurine arabinoside (ara-M) against varicella-zoster virus ryZV) has been previously described (Averett et al, 1991). In the present report, we describe studies on the ability of the arabinosides of hypoxanthine, adenine, 6-methoxypurine, and 6-ethoxypurine to inhibit the growth of erythroid and granulocyte-macrophage progenitor cells in vitro.…”
Section: Introductionmentioning
confidence: 90%
“…In fact, the use of antibiotics and antineoplastic agents has demonstrated that combination therapy with several agents is often the most effective approach and results in equal or superior efficacy with reduced toxicity at lower doses for each agent. To date, numerous combinations of compounds, with the same (convergent) or different (divergent) antiviral targets, have been identified which exhibit synergistic anti-HIV-1 activity, at least in cell culture (Hartshorn et al, 1986;Johnson et al, 1989b;Johnson et al, 1990;Dornsife et al, 1991;Pan et al, 1992;Koup et el., 1993). Some groups have proposed that convergent combination therapy may be the most appropriate for the treatment of HIV infections, by virtue of the fact that multiple mutations in the same viral gene should cause the total compromise of an essential viral enzyme function.…”
Section: Discussionmentioning
confidence: 99%